Expresiile se mai scriu:
a) [tex] 10^{-3} * 10^{-5} [/tex]=[tex] 10^{-8} [/tex]
b) [tex] (2* 10^{-1} )^{2} [/tex]*[tex] (2* 10^{-1} )^{3} [/tex]*([tex]2* 10^{-1} [/tex])=
=[tex] 2^{6} * 10^{-6} [/tex]=[tex] 2^{6} * (2*5)^{-6} [/tex]=
=[tex] 2^{6} * 2^{-6} * 5^{-6} [/tex]=[tex] 5^{-6} [/tex]
c) [tex] (3* 10^{-1} )^{7} [/tex]=[tex] 3^{7} * 10^{-7} [/tex]
d) [tex] (4* 10^{-1} )^{8} [/tex]=[tex] 4^{8} * 10^{-8} [/tex]=
=[tex] ( 2^{2} )^{8} * (2*5)^{-8} [/tex]=[tex] 2^{16} * 2^{-8} * 5^{-8} [/tex]=
=[tex] 2^{8} * 5^{-8} [/tex]
e) [tex] (5* 10^{-1} )^{0} [/tex]*[tex] (5* 10^{-1} )^{2} [/tex]*([tex]5* 10^{-1} [/tex])=
=[tex] 5^{3} * 10^{-3} [/tex]=[tex] 5^{3} * (2*5)^{-3} [/tex]=
=[tex] 5^{3} * 2^{-3} * 5^{-3} [/tex]=[tex] 2^{-3} [/tex]
f) [tex] 10^{-1} * 10^{-5} [/tex]=[tex] 10^{-6} [/tex]